2001
DOI: 10.1557/jmr.2001.0300
|View full text |Cite
|
Sign up to set email alerts
|

Highly (111)-oriented and conformal iridium films by liquid source metalorganic chemical vapor deposition

Abstract: Highly (111)-oriented and conformal iridium (Ir) films were deposited by a liquid source metalorganic-chemical-vapor-deposition process on various substrates. An oxygen-assisted pyrolysis of (methylcyclopentadienyl) (1,5-cyclooctadiene) Ir precursor at a wide range of substrate temperatures (Tsub) between 300 and 700 °C was used. At a low Tsub of 350 °C, the randomly oriented polycrystalline films exhibited an I111/I200 x-ray intensity ratio of 6. However, the films deposited at Tsub = 700 °C on native SiO2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…[34][35][36] Direct liquid injection may produce highly (111)-oriented iridium films on SiO 2 /Si(100) substrates. 37) Decomposition studies in a direct liquid injection CVD process revealed that the reaction temperature of (MeCp)Ir(1,5-COD) decreased from 760 K to below 465 K in the presence of oxygen gas. 37) Because of its attractive properties, decomposition of (MeCp)Ir(1,5-COD) in the absence of oxygen has been additionally studied to clarify the surface reactions that take place on a rhodium surface.…”
Section: Cyclooctadienyl Iridium Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…[34][35][36] Direct liquid injection may produce highly (111)-oriented iridium films on SiO 2 /Si(100) substrates. 37) Decomposition studies in a direct liquid injection CVD process revealed that the reaction temperature of (MeCp)Ir(1,5-COD) decreased from 760 K to below 465 K in the presence of oxygen gas. 37) Because of its attractive properties, decomposition of (MeCp)Ir(1,5-COD) in the absence of oxygen has been additionally studied to clarify the surface reactions that take place on a rhodium surface.…”
Section: Cyclooctadienyl Iridium Complexesmentioning
confidence: 99%
“…37) Decomposition studies in a direct liquid injection CVD process revealed that the reaction temperature of (MeCp)Ir(1,5-COD) decreased from 760 K to below 465 K in the presence of oxygen gas. 37) Because of its attractive properties, decomposition of (MeCp)Ir(1,5-COD) in the absence of oxygen has been additionally studied to clarify the surface reactions that take place on a rhodium surface. [37][38][39] [Ir(acetate)(1,5-COD)] 2 is the only one complex reported to yield high-purity iridium films (<1 mass%C or O) without the need of a reactive gas (either hydrogen or oxygen).…”
Section: Cyclooctadienyl Iridium Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…This was due to the fact that the plane with minimum surface energy was (111); the coating was most stable if oriented toward (111). Goswami et al [20] indicated that (111)-oriented Ir coating exhibited excellent diffusionbarrier properties against oxygen. Wessling et al [21] researched the effects of incident atom energy on preferred crystallographic orientation of the MS Ir film.…”
Section: Resultsmentioning
confidence: 99%
“…The ratio decreases at lower and higher deposition temperatures. For comparison, highly (111) oriented Ir thin films deposited by liquid-injection MOCVD were obtained by Goswami et al [39] attaining values as high as I111/I200 = 277 on Si(100) substrates with native oxide. This at least indicates that the predominant crystal growth proceeds along the (111) orientation parallel to the substrate for higher deposition temperatures.…”
Section: Xrd and Xrrmentioning
confidence: 99%